Quality Economic Growth: Is It Possible to Achieve by An Archipelago Area? - Telaumbanua, Ya'aman (Pelopor Publikasi Akademika, 2024)
The purpose of this study, the researcher uses descriptive and verifiable analysis methods. Verifiable analysis through panel data regression analysis, by choosing the best approach from the Common Effect Model, Fixed Effect Model or Random Effect Model. The research variables consisted of natural resource factors (F_SDA) in the primary sector which were proxied from the contribution of the agriculture, forestry and fisheries sectors as well as the mining and quarrying sector to GDP, Foreign Investment (FDI), Government Expenditure (Blj_P), Average School Length (R_LS), Population Growth (Pert_Pduk) as free variables and Economic Growth (Pert_Ek) and Employment Opportunity Rate (TKK). Secondary data was obtained from BPS, the Ministry of Finance of the Republic of Indonesia, SatuData of the Ministry of Manpower. The type of data is panel data that was studied during the time period 2010 to 2019. The results of the study show that relatively high economic growth in areas with archipelagic characteristics does not have an impact on increasing employment opportunities. The F_SDA and FDI variables have no effect on economic growth in archipelagic areas, the Blj_P variables are influential and significant, while Pert_Pduk have an effect but not significantly on economic growth in archipelagic areas. The human resource factor variable that is proxied from the average of a long time (R_LS) has an effect but is negative and significant on economic growth in the archipelago. Overall, from this study, it was found that economic growth in the archipelago during the period from 2010 to 2019 was not of good quality.